Draw 50 dogs the step-by-step way to draw beagles, German shepherds, collies, golden retrievers, yorkies, pugs, malamutes, and many more ... - Ames, Lee J. (New York : Watson-Guptill Publications, 2012)
Provides step-by-step instructions for drawing fifty different breeds of dogs.
Originally published in trade paperback in the United States: New York : Doubleday, 1981.
8 - 12 years
Keywords: Dogs in art; Drawing -- Technique; Juvenile works